Underachievement in education, children at risk of poverty and social expenditures of local budgets: Empirical analysis of the EU countries - Klapkiv, Jurij; Malyniak, Bohdan; Martyniuk, Olesia (<center>Conference Proceedings Determinants Of Regional Development</center>; No 2 (2021): Conference Proceedings - VIII International Scientific Conference Determinants of Regional DevelopmentDO - 10.14595/CP/02/025, 2021)
The implementation of important sustainable development goals is closely linked to budget-financed provision of public goods. Numerous scientific studies prove the importance of quality education for the development of up-to-date competences and encouragement of a frugal attitude towards natural environment. This is the reason why the level of underachievement in reading, maths or science is included in the system of indicators used to assess the progress made in the attainment of sustainable development goals. The acquisition of education is a multi-faceted complex process, which is affected by a range of social factors. The unassailable fact is that low level of household well-being produces a negative impact on the capabilities of children to acquire proper education. The goal of this study is to reveal the nature of the relationship between the level of underachievement in reading, maths or science and the percentage of children at risk of poverty or social exclusion, on the one hand, and social expenditures of budgets, on the other. Thus, by applying panel data analysis on a set of empirical data for 28 countries of the European Union over the period from 2007 to 2018, we studied the impact of budget expenditures, including expenditures of local budgets on pre-primary and primary education, secondary education and social protection of families with children, on the outcome variables. The findings revealed that larger expenditures on secondary education allocated from both local budgets (the coefficient of dependence equal to (–4.87)) and state and regional budgets (the coefficients of dependence equal to (–3.34)) produce an inverse impact on the level of underachievement in reading, maths or science. Besides, we find that the level of underachievement in reading, maths or science decreases as a result of increases in local budget expenditures on pre-primary and primary education (the coefficient of dependence equal to (–2.11)) and increases in local budget expenditures on social protection of families and children (–1.9). The study also finds support for the inverse impact of local budget expenditures on social protection of families and children (the coefficient of dependence equal to (–4.38)) and pre-primary and primary education (the coefficient of dependence equal to (–2.16)) on the percentage of children at risk of poverty or social exclusion. The findings of this research can be used for planning and implementing measures aimed at the realization of SDG objectives, as well as for modelling effective budget policies.